Analysis of Antioxidant Consumption, Body Mass Index and the Waist-Hip Ratio in Early Postmenopause - Carlos A. Jiménez-Zamarripa; Liliana Anguiano-Robledo; Patricia Loranca-Moreno; M. Esther Ocharan-Hernández; Claudia C. Calzada-Mendoza (Medical Sciences, 2019)
Oxidative stress is present in early postmenopause. Antioxidants, present in food, avoid or limit the damage caused by free radicals. The aim of this study was to analyze whether the consumption of vitamin A, vitamin C, and Selenium was adequate in postmenopausal women and its relationship with levels of malondialdehyde. A descriptive, cross-sectional prospective clinical study was carried out with 132 women (45–55 years old) in postmenopause. The body mass index (BMI) and the waist-to-hip ratio (WHR) were calculated. The participants were surveyed about their food consumption for seven days. The plasmatic concentration of malondialdehyde was quantified by the methyl-phenyl-indole method. The women were grouped according to their BMI. All groups showed similar consumption of proteins, lipids, and carbohydrates, which exceeded the daily recommended level. According to the WHR, 87% had android fat distribution. Selenium, vitamin C, and vitamin A intake were below the daily recommended/suggested levels. The greater the BMI, the higher the plasmatic concentration of malondialdehyde in the patients. It was observed an elevated caloric intake, android fat distribution, and a greater BMI was accompanied by a lower consumption of antioxidants and an increased level of malondialdehyde.